Bacterial and extracellular polysaccharide content of brine‐wetted snow over Arctic winter first‐year sea ice. Issue 2 (11th February 2013) - Ewert, M.; Carpenter, S. D.; Colangelo‐Lillis, J.; Deming, J. W.
Abstract: [1] During freeze‐up and consolidation, sea ice rejects to its surface brine of marine origin that is incorporated into overlying snow. To evaluate the transport of biological components in brines from ice to snow, vertical profiles of temperature, salinity, bacterial abundance, and extracellular polysaccharide substances (EPS) were obtained through snow and first‐year sea ice (Barrow, AK) in consecutive winters (2010, 2011). Snow profiles showed strong interannual variation, with 2010 presenting higher values and wider ranges in salinity (0.3–30.9, practical salinity), bacterial abundance (2.8 × 10 2 –1.5 × 10 4 cells mL − 1 ), and particulate EPS (pEPS, 0.04–0.23 glucose equivalents (glu‐eq) mg L − 1 ) than 2011 (0–11.9, 2.7 × 10 3 –4.2 × 10 3 cells mL − 1 and 0.04–0.09 glu‐eq mg L − 1, respectively). Surface ice also differed interannually, with 2010 presenting again higher salinity (19.4, n  = 1), bacterial abundance (5.4 × 10 4 –9.6 × 10 4 cells mL − 1 ) and pEPS (0.13–0.51 glu‐eq mg L − 1 ) than 2011 (7.7–11.9, 1.7 × 10 4 –2.2 × 10 4 cells mL − 1, and 0.01–0.09 glu‐eq mg L − 1, respectively). Transport of bacteria and pEPS from sea‐ice brines into snow was evident in 2010 but not 2011, a year with more extreme winter conditions of colder temperature, thinner snow, and stronger wind. By size fraction, the smallest EPS (< 0.1 µm) dominated (> 80%) total EPS in both ice and snow; the > 3 µm fraction of EPS in snow appeared to have an atmospheric source. Evaluation of membrane integrity by Live/Dead stain revealed a high percentage (85%) of live bacteria in saline snow, identifying this vast environment as a previously unrecognized microbial habitat. Key Points: Upward brine transport delivers bacteria and exopolymers from sea‐ice into snow Bacteria and sugars did not always move proportionately with salts Environmental conditions influence bacterial transport and persistence in snow